2018
DOI: 10.1186/s13071-018-2799-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the in vitro susceptibility of Loa loa microfilariae to drugs commonly used in parasitological infections

Abstract: BackgroundCo-infection with loiasis remains a potential problem in control programs targeting filarial infections. The effects of many anti-parasitic drugs often administered to Loa loa infected people are not well documented. This study compared the in vitro activity of several of these drugs on the viability of L. loa microfilariae (mf).MethodsHuman strain L. loa mf were isolated from baboon blood using iso-osmotic Percoll gradient, and cultured in RPMI 1640/10% FBS with antimalarial drugs (mefloquine, amodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…In addition, mefloquine was active against Opisthorchis viverrini in vitro and in hamsters ( Keiser et al, 2009b ), but not in human patients ( Soukhathammavong et al, 2011 ). Against nematodes, mefloquine was active in vitro against adults and microfilariae of Brugia patei and B. malayi ( Walter et al, 1987 ), against Onchocerca gutturosa ( Townson et al, 1990 ), against microfilariae of Loa loa ( Njouendou et al, 2018 ), and against Mansonella perstans microfilariae ( Njouendou et al, 2019 ). Overall, mefloquine shows activity against a variety of helminth parasite species.…”
Section: Mefloquinementioning
confidence: 99%
“…In addition, mefloquine was active against Opisthorchis viverrini in vitro and in hamsters ( Keiser et al, 2009b ), but not in human patients ( Soukhathammavong et al, 2011 ). Against nematodes, mefloquine was active in vitro against adults and microfilariae of Brugia patei and B. malayi ( Walter et al, 1987 ), against Onchocerca gutturosa ( Townson et al, 1990 ), against microfilariae of Loa loa ( Njouendou et al, 2018 ), and against Mansonella perstans microfilariae ( Njouendou et al, 2019 ). Overall, mefloquine shows activity against a variety of helminth parasite species.…”
Section: Mefloquinementioning
confidence: 99%
“…Loiasis remains an important public health issue, and treatment options are limited due to severe adverse events [4, 5]. However, it has been shown that FLBZ, know essentially as a macrofilaricidal agent drug [16, 17], exhibits little or no microfilaridal activity against several filarial species, such as Brugia pahangi [18], Onchocerca lienalis [19] and L. loa [20], and its capacity in eliminating adult worms has been elucidated in many studies for filarial species such as B. pahangi [18, 21], Breinlia booliati [22] and Onchocerca ochengi [23]. In this study, we showed that FLBZ reduces worm motility from 80.5% to 14.5% by 9 days after incubation at concentrations of 0.05–10 μg/ml, using the recently published filarial in vitro culture system that has been shown to promote development and moulting of infective stages of L. loa [13] and M. perstans [12].…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood samples (4 ml) were collected from a donor infected with L. loa and MF were obtained using version of a previously described protocol [20,21]. In brief, 2 ml of whole blood was layered onto 2 ml-modified Percoll gradient (Sigma-Aldrich) in a 15-ml tube (Falcon) and centrifuged at 2000× rpm for 20 min without brake using a bench-top centrifuge (Human Diagnostics, Wiesbaden, Germany).…”
Section: Isolation Of Loa Loa Microfilariae From Human Peripheral Bloodmentioning
confidence: 99%